الإستراتيجية الاقتصادية الصينية في المنطقة المغاربية -الفرص والمحاذير بالنسبة لدول المنطقة- - حسين , قوادرة (Finance and Business Economies Review, 2017)
<span dir="ltr" style="left: calc(var(--scale-factor)*56.40px); top: calc(var(--scale-factor)*408.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922069);" role="presentation">While relations between China and Mag<span dir="ltr" style="left: calc(var(--scale-factor)*219.05px); top: calc(var(--scale-factor)*408.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913371);" role="presentation">hreb countries are old, their increase underlines the emergence of <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*419.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.959652);" role="presentation">a multipolar world and the displacement of centre of gravity of the global economy. <span dir="ltr" style="left: calc(var(--scale-factor)*405.82px); top: calc(var(--scale-factor)*419.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925216);" role="presentation">These relations are <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*431.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93732);" role="presentation">mainly economic and established on the principle of “win-<span dir="ltr" style="left: calc(var(--scale-factor)*291.19px); top: calc(var(--scale-factor)*431.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918793);" role="presentation">win”. They are based on spec<span dir="ltr" style="left: calc(var(--scale-factor)*411.58px); top: calc(var(--scale-factor)*431.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924426);" role="presentation">ialization between <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*442.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936127);" role="presentation">Maghreb countries <span dir="ltr" style="left: calc(var(--scale-factor)*134.66px); top: calc(var(--scale-factor)*442.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.95442);" role="presentation">suppliers of raw materials, and <span dir="ltr" style="left: calc(var(--scale-factor)*267.17px); top: calc(var(--scale-factor)*442.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928046);" role="presentation">Manufactured goods and <span dir="ltr" style="left: calc(var(--scale-factor)*373.03px); top: calc(var(--scale-factor)*442.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934453);" role="presentation">services providers from the <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*454.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883445);" role="presentation">Chinese side.<span dir="ltr" style="left: calc(var(--scale-factor)*107.30px); top: calc(var(--scale-factor)*454.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9178);" role="presentation">. The military partnerships have also been developed. Thus China brings opportunities for the <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*465.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904227);" role="presentation">development of the region. <span dir="ltr" style="left: calc(var(--scale-factor)*69.02px); top: calc(var(--scale-factor)*477.43px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933081);" role="presentation">However, China’s economic presence in the <span dir="ltr" style="left: calc(var(--scale-factor)*256.38px); top: calc(var(--scale-factor)*477.43px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.977715);" role="presentation">Magreb region is not without risks on the long run if it <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*488.95px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.02682);" role="presentation">fails to pull the local economy and be in conformity with human rights, environmental and social <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*500.47px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903492);" role="presentation">standards, or the good governance.